Inter‐Cloud architectures and application brokering: taxonomy and survey. (12th December 2012) - Grozev, Nikolay; Buyya, Rajkumar; Garbervetsky, Diego; Kim, Sunghun
SUMMARY Although Cloud computing itself has many open problems, researchers in the field have already made the leap to envision Inter‐Cloud computing. Their goal is to achieve better overall Quality of Service (QoS), reliability and cost efficiency by utilizing multiple clouds. Inter‐Cloud research is still in its infancy, and the body of knowledge in the area has not been well defined yet. In this work, we propose and motivate taxonomies for Inter‐Cloud architectures and application brokering mechanisms. We present a detailed survey of the state of the art in terms of both academic and industry developments (20 projects), and we fit each project onto the discussed taxonomies. We discuss how the current Inter‐Cloud environments facilitate brokering of distributed applications across clouds considering their nonfunctional requirements. Finally, we analyse the existing works and identify open challenges and trends in the area of Inter‐Cloud application brokering. Copyright © 2012 John Wiley & Sons, Ltd.